Strategi Guru PAI Dalam Meningkatkan Minat Belajar Siswa Pada Pelajaran PAI Di SD Plus Citra Madinatul Ilmi Banjarbaru - Siti Rahmawati (STAI AL FALAH Banjarbaru, 2021)
This study discusses the strategy of PAI teachers in increasing students' interest in learning in PAI lessons at SD Plus Citra Madinatul Ilmi Banjarbaru. The purpose of this study was to determine the strategies of PAI teachers in increasing students' interest in learning in PAI lessons as well as factors that support and hinder PAI teachers' strategies in increasing students' interest in learning PAI at SD Plus Citra Madinatul Ilmi Banjarbaru. The subjects in this study were PAI teachers at SD Plus Citra Madinatul Ilmi Banjarbaru. While the object of this research is the strategy of PAI teachers in increasing students' interest in learning in PAI lessons as well as factors that support and hinder PAI teachers' strategies in increasing students' interest in learning in PAI lessons at SD Plus Citra Madinatul Ilmi. Data collection techniques used are observation, interviews and documentation. While data processing is done by editing, data classification and data interpretation. Furthermore, it was analyzed descriptively and qualitatively and concluded by the inductive way. Based on the results of the study, it is known that the PAI teacher's strategy in increasing students' interest in learning in PAI lessons at SD Plus Citra Madinatul Ilmi has been implemented well. This can be proven from the strategies used by PAI teachers in the form of always trying to actively involve students in the learning process, focusing students' attention, providing motivation, cooperative and individualization principles and demonstrations in teaching. In addition, the strategy of PAI teachers in increasing students' interest in learning in PAI lessons can be influenced by several factors, namely feelings of pleasure towards the material, the level of awareness of students about the need to study PAI, student concentration, parental support and facilities provided by the school. Keywords: Learning strategy, PAI teacher, learning interest.